Capacitação em serviço de arquivo: o arquivista frente aos desfios das novas tecnologias de informação e comunicação - Andrade, Andresa Leia de [UNESP]; Almeida, Daniela Pereira dos Reis de [UNESP] (My University, 2011)
The professional archivist must be able to acquire apprenticeship and to pass his team of work, fulfilling so in satisfactory way his to do inside the institution which works, making possible, the use, the dissemination, organization, recuperation of the information. Since an enabled, well prepared professional develops of doing his efficient way inside the organization (or institution), and it bears in mind what must always be updated and prepared so the new technologies of the information and communication changes are in constant, therefore the professional of the information (archivist) must be constantly looking for apprenticeship, to be enabled through the continued education.

O profissional arquivista deve ser capaz de adquirir aprendizado e passar a sua equipe de trabalho ,desempenhando assim de modo satisfatório o seu fazer dentro da instituição a qual trabalha, possibilitando o uso, a disseminação, organização, recuperação da informação. Pois um profissional capacitado, bem preparado desenvolve de modo eficiente seu fazer dentro da organização (ou instituição), e tem em mente que sempre deve estar atualizado e preparado, pois as novas tecnologias da informação e comunicação estão em constantes mudanças, por isso o profissional da informação (arquivista) deve estar constantemente buscando aprendizado, se capacitar através da educação continuada.